Comparison of postoperative complications and facial nerve recovery rates after conventional and partial superficial parotidectomy of benign parotid tumours: a prospective study. Issue 3 (March 2021) - Al-Aroomi, M.A.; Mashrah, M.A.; Abotaleb, B.M.; Sun, J.; Al-Worafi, N.A.; Huang, Y.; Xie, F.
Abstract: The aim of this study was to compare postoperative complications and facial nerve (FN) recovery rates between conventional superficial parotidectomy (CSP) and partial superficial parotidectomy (PSP) as surgical treatment for benign parotid tumours. A prospective study was conducted on 55 consecutive patients who underwent either CSP ( n  = 35) or PSP ( n  = 20) for benign parotid tumours. The primary outcomes were FN injury, FN recovery rates, and Frey syndrome. Secondary outcomes were operative time, hospital stay, sialocele, haematoma, and auricular numbness. The degree of FN injury was evaluated at 1 week, 1, 3, 6, and 12 months postoperative using the House–Brackmann grading system. Frey syndrome was assessed using a subjective clinical questionnaire and objective Minor starch–iodine test. No patient in either group experienced permanent FN paralysis. There was a significantly higher incidence of temporary FN weakness in the CSP group ( P  = 0.007). The respective FN recovery rates at 1, 3, 6, and 12 months were 60%, 88.6%, 94.3%, and 100% in the CSP group and 90%, 95%, 100%, and 100% in the PSP group. No significant difference was observed between the groups regarding the incidence of Frey syndrome, sialocele, and haematoma. The operative time and hospital stay were both shorter in the PSP group. Although the PSP is a more conservative procedure with significantly reduced FN injury, operative time, and hospital stay compared to CSP, the CSP procedure shows a comparable FN recovery rate to the PSP.